Legionella pneumophila modulates the host cytoskeleton by an effector of transglutaminase activity - Yan Liu; Yao Liu; Zhao‐Qing Luo (mLife, 2025)
Abstract The bacterial pathogen Legionella pneumophila delivers more than 330 effector proteins into host cells through its Dot/Icm type IV secretion system (T4SS) to facilitate its intracellular replication. A number of these effectors modulate organelle trafficking pathways to create a membrane‐bound niche called the Legionella‐containing vacuole (LCV). In this study, we found that L. pneumophila induces F‐actin accumulation in the host cell cortex by its Dot/Icm substrate RavJ (Lpg0944). RavJ harbors a C101H138D170 motif associated with human tissue transglutaminases (TGs). We show that RavJ catalyzes a covalent linkage between actin and members of the Motin family of proteins, including Angiomotin (AMOT) and Angiomotin‐like 1 (AMOTL1), which are known to regulate cell migration and contribute to the formation of cellular structures such as endothelial cell junctions and tubes. Further study reveals that RavJ‐induced crosslink between actin and AMOT occurs on its Gln354 residue. Crosslink between actin and AMOT significantly reduces the binding between actin and its binding partner cofilin, suggesting that RavJ inhibits actin depolymerization. We also demonstrate that the metaeffector LegL1 directly interacts with RavJ to antagonize its TG activity, leading to reduced crosslinks between actin and Motin proteins. Our results reveal a novel mechanism of modulating the host actin cytoskeleton by L. pneumophila.